DISIPLIN BELAJAR SISWA KELAS VIII PADA MATA PELAJARAN IPS SMP NEGERI 1 KECAMATAN LINGGO SARI BAGANTI KABUPATEN PESISIR SELATAN - MURNI, ZULPI RINITA (Pendidikan Sosiologi, 2014)
In SMP Negeri 1 Linggo Sari Baganti IPS student learning discipline in class VIII in schools indicate a problem. Formulation of the problem in the study of how the discipline of social studies in the eighth grade students of SMP Negeri 1 Baganti Linggo Sari district. The South Coast. The purpose of this study was to describe the discipline of student learning in social studies and at home in Junior High School eighth grade 1 Linggo Sari Baganti. This study used qualitative methods and descriptive analytic. Informant selection techniques conducted by purposive sampling. Methods of data collection in this study using interviews, observation and documentation. Then that becomes the unit of analysis is the individual. The data has been collected systematically analyzed. The theory used in this study is the theory advanced by Watsons behaviorism.The results of the study confirms that in school, especially in social studies class VIII can be drawn that the discipline learned most students lack discipline. Thus, students of SMP Negeri 1 Linggo Sari Baganti student learning discipline in schools is still low. Thus, students discipline student learning at home is still low. Thus it can be concluded that the low discipline student learning in social studies in grade school. Students should be learning in school discipline in the class of SMP Negeri 1 Linggo Sari Baganti.